2022
DOI: 10.1038/s41598-022-14342-3
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary sinus aeration analysis using computational fluid dynamics

Abstract: The maxillary sinus aeration using the computational fluid dynamics (CFD) method based on individual adult patients’ computed tomography (CT) scans were analyzed. The analysis was based on CT images of 4 patients: one with normal nose anatomy and three with nasal septal deviation (NSD) and concha bullosa (CB). The CFD simulation was performed using the Reynolds-Average Simulation approach and turbulence closure based on linear eddy viscosity supplemented with the two-equation k-$$\omega$$ ω … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Li et al also noted that there were significant differences in maximum airflow velocity, minimal airflow temperature, maximum wall shear stress, and nasal resistance between the deviated side (the narrow side of the nasal meatus) and the nondeviated side of the nasal septum in their hydrodynamic analysis of patients with nasal septum deviation ( 27 ). Tretiakow et al said that the complex nasal meatus structure caused by anatomic variations would change continuous airflow in the healthy nasal cavity so that it becomes volatile ( 28 ). The findings of Li et al revealed a positive correlation between the change in nasal volume and nasal airflow ( 27 ), which also supported our hypothesis that the change of nasal airflow is related to ACP formation.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al also noted that there were significant differences in maximum airflow velocity, minimal airflow temperature, maximum wall shear stress, and nasal resistance between the deviated side (the narrow side of the nasal meatus) and the nondeviated side of the nasal septum in their hydrodynamic analysis of patients with nasal septum deviation ( 27 ). Tretiakow et al said that the complex nasal meatus structure caused by anatomic variations would change continuous airflow in the healthy nasal cavity so that it becomes volatile ( 28 ). The findings of Li et al revealed a positive correlation between the change in nasal volume and nasal airflow ( 27 ), which also supported our hypothesis that the change of nasal airflow is related to ACP formation.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the influence of the mesh on the solution was presented in our previous publication 28 . Moreover, the properties of the mesh and calculation times (Xeon 5120 2.2 GHz processor (13 out of 14 cores involved)) are given in Table 2.…”
Section: Cfdmentioning
confidence: 99%
“…The inlet boundary condition localised at the larynx was specified through the volumetric flow rate corresponding to 5.1 litres per minute 9,28 . It was assumed that the typical breath took 4 seconds and that the exhalation and inhalation phases each lasted 2 seconds.…”
Section: Cfdmentioning
confidence: 99%
See 1 more Smart Citation